The Frog Who Croaked - Krosoczka, Jarrett (New York : Walden Pond Press, 2013)
Paired together after a veteran detective retires, platypus police squad members Rick Zengo, a hotshot rookie, and Corey O'Malley, a hard-nosed old-timer, struggle with their differences while tackling their first case involving a missing schoolteacher and a duffle bag filled with illegal fish.
Keywords: Platypus -- Juvenile fiction; Missing persons -- Juvenile fiction; Fishes -- Juvenile fiction; Detective and mystery stories; Platypus -- Fiction; Missing persons -- Fiction; Fishes -- Fiction; Mystery and detective stories